Odpowiedzi

  • Użytkownik Zadane
2010-02-07T17:29:18+01:00
A) (-3razy 1/4) + (3razy 1/2) +1= -3/4+3/2=-3/4+6/4=3/4

b) √49-(2*8)+3=7-16+3=12
2010-02-07T17:29:22+01:00
Sorry ale umiem tylko "a'
a) -3a²+3a+1 dla a= ½
-3*(¹/₂)² +3*¹/₂ + 1= -3*¹/₄+³/₂+1=-³/₄+⁶/₄+1=1³/₄=1,75
b) ∫x² - 2y³+3z⁴ dla x =-7 y=2 z=1
√-7²-2*2³+3*1=√49-2*8+3=7-16+3=-6
Najlepsza Odpowiedź!
2010-02-07T17:30:07+01:00
A) -3a²+3a+1 dla a= ½ =-3*(1/2)²+3*1/2+1=-3*1/4+3/2+1=-3/4+3/2+1= - 3/4+6/4+1=1i 3/4
b) ∫x² - 2y³+3z⁴ dla x = -7 y=2 z = 1= √-7²-2*2³+3*1=-7-2*8+3=-7-16+3=-20